2015
DOI: 10.1890/es14-00415.1
|View full text |Cite
|
Sign up to set email alerts
|

An ecological engineer maintains consistent spatial patterning, with implications for community‐wide effects

Abstract: Abstract. In many ecosystems, foundational species create spatial patterns that structure a broader community. It is unclear, however, how robust these patterns are across large areas and strong environmental gradients, and how the landscape-level consequences of these patterns may vary. We investigated the robustness of non-random patterning in the dispersion of the western harvester ant (Pogonomyrmex occidentalis), a widely recognized ecosystem engineer of western North America. We used remote imagery to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Ground visits of the plots "T Australia Jiga" and "T Australia Pilb" confirmed that the substrate is as flat and edaphically as homogeneous as for the typical FCs patterns 50 km further to the south . A lack of an effect of topographic or floristic variation on spatial patterns of insect mounds has been also reported for North American harvester ants, which do sometimes inhabit very homogeneous grasslands (Dibner et al, 2015).…”
Section: Factors That May Affect Variability In Patternsmentioning
confidence: 76%
“…Ground visits of the plots "T Australia Jiga" and "T Australia Pilb" confirmed that the substrate is as flat and edaphically as homogeneous as for the typical FCs patterns 50 km further to the south . A lack of an effect of topographic or floristic variation on spatial patterns of insect mounds has been also reported for North American harvester ants, which do sometimes inhabit very homogeneous grasslands (Dibner et al, 2015).…”
Section: Factors That May Affect Variability In Patternsmentioning
confidence: 76%
“…Therefore, the central target of species reintroductions should become their ecological role played in the context of system stability, rather than simply increasing the number of species. In other words, what matters is the functional diversity as well as how it is spatially patterned, even if it is still unclear whether and how spatial patterning of key species varies within most communities (Dibner, Doak & Lombardi, ). In the case studies presented by Hayward et al .…”
mentioning
confidence: 99%
“…, Dibner et al. ). In Australia, we would expect that such ecosystem engineers would cause spatial patterns that are similar to the FCs, if they were the cause.…”
Section: Introductionmentioning
confidence: 98%
“…A regional-scale analysis of the typical signature of termite-created gaps vs. FCs may thus help to shed light on the spatial differences and thereby on the mechanisms driving the formation of the fairy-circle patterns. For example, true ecosystem engineers such as harvester ants create regularly spaced gaps in grass vegetation over a large precipitation range of 200-600 mm annual rainfall in many ecosystems of North America (Nicolai et al 2010, Dibner et al 2015. In Australia, we would expect that such ecosystem engineers would cause spatial patterns that are similar to the FCs, if they were the cause.…”
Section: Introductionmentioning
confidence: 99%